The Effectiveness of Cabbage Leaf Compresses and Aloe Vera Against Breast Engorgement Scales in Breastfeeding Mothers - Masitoh, Siti; Mochartini, Tri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Previous research reported the reason a mother stops breastfeeding her baby in the first month post partum is because of breast engorgement. This has a big impact on exclusive breastfeeding status. Engorgement in the breasts, whatever the cause, must be treated immediately. Providing non-pharmacological therapy must be attempted as initial prevention because the side effects are minimal. The aim of this research is to analyze the effectiveness of cabbage leaf compresses on the scale of breast engorgement in breastfeeding mothers. This research is a type of intervention research with a quasi-experimental design in the work area of the Bandung community health Center, Serang Regency, Banten Province in December 2023. The sample used was 30 breastfeeding mothers. The data was interview, anamnesa, and collected by observational form. The bivariate analysis used in this study was the Mann Whitney U test. The results of the Mann-Whitney test showed a p value of 0.049 < 0.05 for the aloe vera compress, the results of the cabbage leaf compress intervention analysis showed a p value of 0.042 < 0.05, which means there was difference in mean scale breast engorgement before and after applying aloe vera and cabbage leaf compresses.